Agile Nudge University Innovation Forum: solving real-world problems - Barboi, Cristina; Shojaei, Fatemehalsadat; Gardner, Leslie; Stewart, Nick; Shojaei, Fereshtehossadat; Seidman, Mark; Holden, Richard J.; Fowler, Nicole R.; Summanwar, Diana; Stephanian, Brooke; Boustani, Malaz (Frontiers in Public Health, 2025)
IntroductionThe Indiana University Innovation Forum is an online group-based problem-solving platform that brings together physicians, nurses, social workers, patients, healthcare managers, and other key stakeholders to tackle complex healthcare challenges. This study analyzes the data generated during the Agile Nudge University Innovation Forum (ANUIF) events from October 2022 to December 2024.MethodsThis is a mixed-methods study consisting of a quantitative analysis of the ANUIF events, including participant numbers, level of satisfaction, and the number of solutions created, as well as a qualitative appraisal of the solution themes generated by participants.ResultsThe average number of attendees for the Innovation Forums was 14.83 (SD = 6.92), and the mean satisfaction score was 51.56 (SD = 25.08). The average number of generated solutions per forum was 16 (SD = 5.1), with an average of 10.71 (SD = 3.16) main solutions and 4.38 (SD = 3.71) sub-solutions. The average number of old or existing solutions was 6.19 (SD = 2.94), and the average number of novel solutions was 4.52 (SD = 2.44). The administrative changes, followed by the implementation of the ANUIF dashboard and control charts, resulted in significant increases in the number of participants contacted, respondents, registered attendees, and actual attendees. There were significant differences in the average Net Promoter Scores between the attendee cohorts included in the study. The qualitative analysis of Innovation Forums identified five common themes; the most common themes were Adaptive innovation and Collaborative Problem-Solving.DiscussionA streamlined Innovation Forum process ensured a steady number of participants with average satisfaction scores. The attendees generated innovative, generalizable solutions applicable to “real-world” healthcare challenges. Participants generated more than one solution and sub-solutions to the discussed problems, demonstrating an understanding of agile science-based problem-solving, ideation, and innovation.